The english teacher eaudiobook - King, Lily (Recorded Books Inc., 2005)
Unanimously praised for her first novel, The Pleasing Hour, which was called "Splendid ... powerful ... [and] so assured it's hard to believe the book itself is her debut" by The New York Times Book Review, Lily King has written a thrilling successor. In The English Teacher, King uses her superb craftsmanship, effortlessly suspenseful pacing, and tenderly observed insight into marriage, motherhood, and family to expertly limn the life of an independent single mother and her fifteen-year-old son, who is on a circuitous path toward a truth she has long concealed from him. Fifteen years ago Vida Avery arrived alone and pregnant at elite Fayer Academy. She has since become a fixture and one of the best English teachers Fayer has ever had. By living on campus, on an island off the New England coast, Vida has cocooned herself and her son, Peter, from the outside world and from an inside secret. For years she has lived largely through the books she teaches, but when she accepts the impulsive marriage proposal of ardent widower Tom Belou, the prescribed life Vida has constructed is swiftly dismantled. Peter, however, welcomes the changes. Excited to move off campus, eager to have siblings at last, Peter anticipates a regular life with a "normal" family. But the Belou children are still grieving, and the memory of their recently dead mother exerts a powerful hold on the house. As Vida begins teaching her signature book, Tess of the d'Urbervilles, a nineteenth-century tale of an ostracized womanand social injustice, its themes begin to echo eerily in her own life and Peter sees that the mother he perceived as indomitable is collapsing and it is up to him to help. The English Teacher is a passionate tale of a mother and son's vital bond and a provocative look at our notions of intimacy, honesty, loyalty, family, and the real meaning of home. A triumphant and masterful follow-up to her award-winning debut, The English Teacher confirms Lily King as one of the most accomplished and vibrant young voices of today. "Beautifully written and carefully observed ... King is a wildly talented writer."—Claire Dederer, Chicago Tribune